ANALISIS HISTORIS-KOMPARATIF SISTEM PEMBIAYAAN PENDIDIKAN DI ERA KOLONIAL DAN REPUBLIK INDONESIA SERTA IMPLIKASINYA TERHADAP KESETARAAN AKSES PENDIDIKAN - Catur Prida Retnivia; Pratisa Martha Sari; Krista Alisa Meyliani; Wahyu Setiya Ningrum; Widyatmike Gede Mulawarman; Mukhamad Nurhadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the comparative education financing systems between the colonial era and the era of the Unitary State of the Republic of Indonesia (NKRI), as well as their implications for equity in educational access. The study employs a qualitative approach with a historical-comparative design through library research and document analysis of historical archives, education policies, and national and international education statistics. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings indicate that the education financing system during the colonial era was limited, exclusive, and discriminatory, resulting in low educational participation rates among indigenous populations, which remained below 10%. In contrast, during the NKRI era, the education financing system has undergone a significant transformation toward a more inclusive approach, marked by the policy of allocating at least 20% of the national budget (APBN) to education and the implementation of financing programs such as the School Operational Assistance (BOS) and the Indonesia Smart Program (PIP). These initiatives have contributed to a substantial increase in educational access, reaching over 80%. Disparities in educational access persist, particularly between urban and rural areas as well as between developed and underdeveloped regions. These findings suggest that increased education financing has not been fully accompanied by equitable distribution based on needs. The study highlights that while education financing plays a crucial role in expanding access, its effectiveness depends on the adoption of distributive justice principles in resource allocation.